2014
DOI: 10.1162/jocn_a_00660
|View full text |Cite
|
Sign up to set email alerts
|

Fine Neural Tuning for Orthographic Properties of Words Emerges Early in Children Reading Alphabetic Script

Abstract: The left-lateralized N170 component of ERPs for words compared with various control stimuli is considered as an electrophysiological manifestation of visual expertise for written words. To understand the information sensitivity of the effect, researchers distinguish between coarse tuning for words (the N170 amplitude difference between words and symbol strings) and fine tuning for words (the N170 amplitude difference between words and consonant strings). Earlier developmental ERP studies demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
95
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(110 citation statements)
references
References 57 publications
11
95
3
1
Order By: Relevance
“…Results of hierarchical regression analyses showed that Chinese word reading explained significant additional variance in stroke sensitivity after having statistically controlled for age, but age did not explain significant additional variance in stroke sensitivity beyond reading experience. This finding is consistent with previous studies showing that reading experience, rather than age, plays a more important role in learning to read among school-age children (e.g., Burgund et al, 2006; Zhao et al, 2014a). We expected that at an earlier stage of learning to read, e.g., in kindergarten years, maturation should play an equally important role, considering that perception of objects and events in the natural environment is a real-time task and a child needs to have mature sensory primitives (Aslin and Smith, 1988), but finding of the current study did not support this expectation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Results of hierarchical regression analyses showed that Chinese word reading explained significant additional variance in stroke sensitivity after having statistically controlled for age, but age did not explain significant additional variance in stroke sensitivity beyond reading experience. This finding is consistent with previous studies showing that reading experience, rather than age, plays a more important role in learning to read among school-age children (e.g., Burgund et al, 2006; Zhao et al, 2014a). We expected that at an earlier stage of learning to read, e.g., in kindergarten years, maturation should play an equally important role, considering that perception of objects and events in the natural environment is a real-time task and a child needs to have mature sensory primitives (Aslin and Smith, 1988), but finding of the current study did not support this expectation.…”
Section: Discussionsupporting
confidence: 93%
“…It is the first step of visual-orthographic processing that is crucial for reading and learning to read (Maurer and McCandliss, 2007). Recent electrophysiological studies showed that visual expertise for written words correlates with children’s individual reading ability (Zhao et al, 2014a) and that visual word expertise (written word N1) can be observed in young children who has not received formal reading training (Li et al, 2013). It was also reported that dyslexic children showed reduced N1 tuning for written words (Maurer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, children who have learned letters but with developing phonological conversion skills show comparable N170 amplitude in both hemispheres (Kast et al, 2010) or bilateral increase in amplitude against visual control stimuli (Maurer et al, 2006;Zhao et al, 2014). In skilled adult readers, the consistency of letterto-sound correspondences has been shown to influence N170 leftlateralization for pseudowords, which was present in transparent German (Maurer et al, 2005b) but absent in opaque English (Maurer et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%